Antiphospholipid antibody carriers and patients with quiescent antiphospholipid syndrome show persistent subclinical complement activation - Zen, Margherita; Tonello, Marta; Favaro, Maria; Del Ross, Teresa; Calligaro, Antonia; Giollo, Alessandro; Vesentini, Filippo; Gennaio, Ilenia Anna; Arru, Federico; Ruffatti, Amelia; Doria, Andrea (Rheumatology (Oxford, England), 2024)
Objectives Complement activation has been advocated as one mechanism by which aPLs can induce thrombosis. In patients with catastrophic APS or re-thrombosis, enhanced complement activation has been shown, even in the quiescent phase of the disease. We aimed to assess complement activation and to investigate its association with clinical variables in aPL-positive patients with a favourable disease course. Methods Subjects with at least two consecutive positive aPL results obtained ≥12 weeks apart were enrolled. They were subjects without a history of thrombosis or pregnancy morbidity (aPL carriers), patients with pregnancy morbidity alone, i.e. obstetric APS patients (OAPS patients), and/or patients with arterial, venous, or small-vessel thrombotic APS (TAPS patients); for enrolment, all patients were required to have been free of symptoms for ≥2 years. Patients affected with systemic autoimmune diseases were excluded. Healthy age- and sex-matched subjects were included as controls. Plasma C5a and C5b-9 levels were assessed by commercially available ELISA assays. The non-parametric Mann–Whitney test and Spearman’s correlation were applied. Results Thirty-seven OAPS patients, 38 TAPS patients, 42 aPL carriers and 30 healthy subjects were enrolled. The median C5a and C5b-9 levels were significantly higher in quiescent aPL-positive patients (OAPS, TAPS, aPL carriers) compared with controls: C5a ng/ml 10.61 [interquartile range (IQR) 6.87–15.46] vs 4.06 (2.66–7.35), P < 0.001; C5b-9 ng/ml 283.95 (175.8–439.40) vs 165.90 (124.23–236.8), P < 0.001. Similar C5a and C5b-9 levels were observed in OAPS and TAPS patients and aPL carriers. A positive correlation between the median C5b-9 levels and the number of aPL-positive tests was found (P = 0.002). Conclusion The persistence of aPL antibodies is associated with a persistent subclinical activation of the complement cascade.